Subiculum volumes associated with memory function in the oldest‐old individuals aged 95 years and older. Issue 4 (25th February 2019) - Eguchi, Yoko; Noda, Yoshihiro; Nakajima, Shinichiro; Tsugawa, Sakiko; Kida, Hisashi; Plitman, Eric; Graff‐Guerrero, Ariel; Chakravarty, Mallar M; Takayama, Midori; Arai, Yasumichi; Matsuda, Hiroshi; Mimura, Masaru; et al.
Abstract : Aim: Few cohort studies targeting the oldest‐old individuals have been carried out. The subiculum in the hippocampus is thought to be related to memory function, and atrophy of this structure might result in the conversion from amnestic mild cognitive impairment to Alzheimer's disease. Thus, we sought to examine the relationship between subiculum volumes and memory function in individuals aged ≥95 years, using a novel cognitive examination called the Addenbrooke's Cognitive Examination III (ACE‐III) and an advanced magnetic resonance imaging analytical method, Multiple Automatically Generated Templates Brain Segmentation Algorithm (MAGeTbrain), to measure hippocampal subfield volumes. Methods: A part of the cohort data of the Arakawa 95+ study for the oldest‐old aged ≥95 years was used. A total of 10 individuals completed all of the examinations. The MAGeT brain was applied to estimate the subfield volumes of the hippocampus. Correlation analyses and multiple regression analyses were carried out to examine a relationship among ACE‐III memory scores and the subfield volumes in the hippocampus, including the subiculum. Results: There was a significant relationship between ACE‐III memory scores and subdivision volumes. Regression analyses showed that subiculum volumes were associated with ACE‐III memory scores in the oldest‐old individuals (β = 0.721, P = 0.019; F 1, 8 = 8.67, adjusted R 2 = 0.46). Conclusions: The subiculum might play a pivotal role in memory function in the oldest‐old individuals aged ≥95 years. The present finding warrants further research including larger sample sizes. Geriatr Gerontol Int 2019; 19: 347–351 .